02.34 Enhanced conventional cd4+ t cell proliferation in sle is associated with up-regulation of microrna-182 and increased il-7 receptor signalling. (1st March 2017) - Alexander, Tobias; Haftmann, Claudia; Riedel, René; Templin, Lars; Humrich, Jens; Burmester, Gerd-Rüdiger; Radbruch, Andreas; Hiepe, Falk; Mashreghi, Mir-Farzin
Abstract : Background: Recent reports have shown dysregulated microRNAs (miRNAs) in murine models of lupus, among them increased expression of microRNA-182 (miRNA-182), which has been demonstrated to target the transcription factor FOXO1 in activated murine CD4 + T cells, leading to spontaneous T cell activation and clonal expansion. Here we aimed to investigate the expression of miR-182 and FOXO1 in T cells from human SLE patients. Methods: Expression levels of miR-182 were analysed with RT-PCR in purified peripheral blood CD4 + T cells from 9 patients with SLE and age/sex-matched healthy controls (HC). Multicolor flow cytometry was performed to analyse CD4 + T cell expression for FOXO1, Ki-67, Foxp3, the interleukin-7 receptor-α (CD127) and phosphorylated STAT-5a (pSTAT5). Analysis of serum IL-7 levels was performed with ELISA in 27 SLE patients and HC. Induction of miR-182 was assessed in vitro after polyclonal T cell stimulation in the presence of IL-7, and inhibition of T cell proliferation investigated using mir-182 antagomirs. Results: MiRNA-182 was significantly upregulated in CD4 + T cells from SLE patients compared to HC, while the FOXO1 expression was significantly decreased. The percentage of proliferating Ki-67 + conventional Foxp3 - CD4 + T cells TCON was significantly higher in SLE compared to HC (3.85% vs. 1.58%, p<0.001) and their basal pSTAT5 levels significantly enhanced, suggesting a recent stimulation with common gamma chain(γc)-signalling cytokines. SLE TCON displayed decreased expression levels for the FOXO1 target gene CD127 (MFI 2021 vs. 2553, p=0.049) and serum IL-7 levels were significantly higher in SLE compared to HC (17.0 pg/ml vs. 10.2 pg/ml, p=0.001). In vitro, miR-182 could be induced by IL-7, and specific inhibition of miR-182 inhibited T cell proliferation and survival. Conclusion: Our data suggest that enhanced IL7R/STAT5 signalling mediates the induction of miR182 expression, which promotes the proliferation of conventional Foxp3 - T cells SLE. Collectively, our data provide new insights in the pathophysiology of T cell hyperactivity in SLE and identifies miR-182 as a candidate target for future therapeutic approaches.